RELATIONSHIP BETWEEN CLIMATIC CONDITION AND MANGROVE FOREST STRUCTURE ON NORTHERN COAST OF VIETNAM - Tinh, Pham Hong; Hanh, Nguyen Thi Hong; Tuan, Mai Sy (Vietnam Journal of Science and Technology, 2016)
The differences in mangrove forest structure, climate, and the linear relationship between climate and mangrove forest structure on the northern coast of Vietnam were analyzed using mangrove forest data measured in 28 sample plots (Dong Rui-8, Xuan Thuy National Park-12 and Lach Sung-8) and climate data collected at the meteorological stations near the study sites (Dong Rui-Tien Yen station, Xuan Thuy National Park-Van Ly station and Lach Sung-Thanh Hoa station) in the period of 1994 - 2012. Results showed that the differences in mangrove forest structure (stem diameter, biomass and basal area) and climate (temperature and rainfall) among study sites were significant (p < 0.05). Stem diameter, tree height, basal area and biomass had positive linear relationship with annual average temperature and January average temperature, and negative linear relationship with annual rainfall. A consistently low regression coefficient of less than 0.66 was found among the variables. However, all the regression models were statistically significant (p < 0.05). The results could be used to develop multiple linear regression models to predict the change of mangrove ecosystems.